PENILAIAN DIMENSI TUBUH SEBAGAI SALAH SATU PREDIKSI KEKURANGAN NUTRISI PADA IBU MENYUSUI DAN BAYINYA DI KECAMATAN MOYO HULU - Ratna Nurmalita Sari; Dwi Aprilian Nur Putri; Lukman Azis (The Journal of Teknologi Pangan, 2022)
Breastfeeding is recommended way of feeding directly from mother to baby. Newborns are recommended to be exclusively breastfed for at least six months to two years. Nutritional vulnerability to breastfeeding mothers and infants has an impact on nutritional deficiencies such as lack of magnesium, vitamin B6, folate, calcium, and zinc. Prediction of stunting can be conducted by measuring the baby body dimensions such as head circumference, height, and body weight. This study aimed to determine body dimensions as a method of predicting nutritional deficiencies in breastfeeding mothers and their babies in Moyo Hulu District, Sumbawa. This study used a cross sectional study method which carried on 15 breastfeeding mothers and their babies. The assessment was carried out using the WHO Anthro apps. The results showed that breastfeeding mothers in Moyo Hulu District had an average BMI of 21.95%. This showed that breastfeeding mothers in Moyo Hulu District have a normal BMI. Therefore, the baby was included in 3 anthropometric categories, including BMI-for-Age-Z score (BAZ), Height-for-Age-Z score (HAZ), and Weight-for-Age-Z score (WAZ). There were 2 categories of BAZ in infants in Moyo Hulu District, namely obesity with an average of 26.67%, and normal with an average of 73.33%. There were also 2 categories of HAZ in infants, including the normal category with an average of 53.33% and stunted to very stunted with an average of 46.67%. There were 3 categories of WAZ in infants, namely normal with an average of 86.67%, thin with an average of 6.67%, and very thin with an average of 6.67%.